Liver transplantation utilizing mixed biologic and synthetic arterial conduits - Chedid, Márcio Fernandes (2016)
Arterial conduits are necessary in nearly 5% of all liver transplants and are usually constructed utilizing segments of donor iliac artery. However, available segments of donor iliac artery may not be lengthy enough or may not possess enough quality to enable its inclusion in the conduit. Although there are few reports of arterial conduits constructed solely utilizing prosthetic material, no previous reports of conduits composed of a segment of donor iliac artery and prosthetic material (mixed biologic and synthetic arterial conduits) were found in the medial literature to date. Two cases reporting successful outcomes after creation of mixed biologic and prosthetic arterial conduits are outlined in this report. Reason for creation of conduits was complete intimal dissection of the recipient’s hepatic artery in both cases. In both cases, available segments of donor iliac artery were not lengthy enough to bridge infrarenal aorta to porta hepatis. Both patients have patent conduits and normally functioning liver allografts, respectively, at 4 and 31 months after transplant.Mixed biologic and synthetic arterial conduits constitute a viable technical option and may offer potential advantages over fully prosthetic arterial conduits.